Treatment of wastewater from x-ray department (Effluent) using sequencing batch reactor technology - 404516 Wan Norazrina Wan Rusli; Ismail Mahmood, (supervisor) (Skudai : Universiti Teknologi Malaysia, 2008)
Project Paper (Sarjana Muda Kejuruteraan Kimia) - Universiti Teknologi Malaysia, 2008